DEVELOPMENT OF TRADE AND ECONOMIC COOPERATION BETWEEN UZBEKISTAN AND AZERBAIJAN - Abdullaev Ravshan Vakhidovich (Scholar Express Journals, 2025)
This article analyzes the development of trade and economic cooperation between Uzbekistan and Azerbaijan within the framework of the Economic Cooperation Organization (ECO). It examines the dynamics of mutual trade from 2016 to 2024, the structure of exports and imports, as well as the growth of mutual investments and joint projects. Special attention is given to transport, logistics, and energy initiatives, along with prospects for cooperation in tourism. The author emphasizes the strategic nature of the partnership and forecasts that trade turnover will reach $1 billion in the medium term.
Keywords: Economic Cooperation Organization; free trade regime